2019
DOI: 10.3390/e21010049
|View full text |Cite
|
Sign up to set email alerts
|

The von Neumann Entropy for Mixed States

Abstract: The Araki-Lieb inequality is commonly used to calculate the entropy of subsystems when they are initially in pure states as this forces the entropy of the two subsystems to be equal after the complete system evolves. Then, it is easy to calculate the entropy of a large subsystem by finding the entropy of the small one. To the best of our knowledge, there does not exist a way of calculating the entropy when one of the subsystems is initially in a mixed state. We show here that it is possible to use the Araki-Li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…By having the density operator, one can calculate all quantum coherence properties or entanglement criteria. Although there are many references which addressed two-qubit entropy measures (Anaya-Contreras et al 2019;Khordad and Servatkhah 2017;Friis et al 2017;Rehman and Shin 2019), but, very recently, it has been theoretically developed and experimentally demonstrated a new method, resourceand computationally efficient, for quantum state tomography in Fock basis via Wigner function reconstruction and semidefinite programming (Nehra et al 2020). They have shown that obtained density operator from this method is robust against the noise of measurement and relies on no approximate state displacements, and requires all physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…By having the density operator, one can calculate all quantum coherence properties or entanglement criteria. Although there are many references which addressed two-qubit entropy measures (Anaya-Contreras et al 2019;Khordad and Servatkhah 2017;Friis et al 2017;Rehman and Shin 2019), but, very recently, it has been theoretically developed and experimentally demonstrated a new method, resourceand computationally efficient, for quantum state tomography in Fock basis via Wigner function reconstruction and semidefinite programming (Nehra et al 2020). They have shown that obtained density operator from this method is robust against the noise of measurement and relies on no approximate state displacements, and requires all physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…We note that Anaya-Contreras et al have proposed a method to calculate the von Neumann entropy of a larger system from the entropy of a subsystem that is initially in a mixed state. 181…”
Section: Circuit For Schrödinger's Cat States Von Neumann Entropy And...mentioning
confidence: 99%
“…In general, the maximum value of S N is ln N, where N is the number of states of one qubit. The system will be maximally entangled when all the probability amplitudes c m , for m = 1, 2, ...N, reach the same value, c m = 1/N [32].…”
Section: Maximally Entangled States and Entanglement Entropymentioning
confidence: 99%